Handwashing with soap training for elementary school children along the Martapura riverbank - Husnul Khatimah; Fakhrurrazy Fakhrurrazy; Fauzan Muttaqien; Fahrina Ulfah; Siti Khairiyah; Ida Yuliana; Irfan Maulana (Community Empowerment, 2024)
Handwashing with soap, when practiced correctly, is the simplest and most effective way to prevent the spread of fecal-oral and other diseases among children. One of the national elementary school health programs is handwashing with soap (CTPS). Therefore, the purpose of this community service activity is to improve the handwashing skills of elementary school children living near the Martapura River. The methods used were lectures with question-and-answer sessions, demonstrations, focus group discussions, and practice. The results of this activity showed an increase in understanding and skills related to CTPS, so that children know the benefits and procedures.